PANDANGAN RASHĪD RIḌĀ TERHADAP ISRĀILIYĀT DAN AL-KITAB DALAM TAFSĪR AL-MANĀR - Muhammad Akrom Adabi; Abdullah Mubarok (AL ITQAN: Jurnal Studi Al-Qur'an, 2016)
This paper studies on RashÄ«d Riá¸Äâ€™s view on isrÄiliyyÄt and the Bible in his tafsir al-ManÄr. As a reformer in the field of exegesis, Riá¸Ä found urgent necessity in returning al-Qurâ€™an to its original purpose which is to give guidance. The problem is that Riá¸Ä saw many authors of exegesis work (mufassir) before him give profuse and unnecessary exegetical discussion. To Riá¸Ä, displaying this kind of lavish information diverts from the original vision of al-Qurâ€™an and cannot be tolerated. In this case, Riá¸Ä resolutely opposes the quotation of isrÄiliyyÄt. Interestingly, behind this stance, Riá¸Ä quotes the Bible in his work. This becomes the main focus of this study; how Riá¸Ä views isrÄiliyyÄt and the Bible, what is the essential difference between the two according to Riá¸Ä, and what is the reason behind his quotation of the bible and his opposition against isrÄiliyyÄt?. To analyze this topic, descriptive-analytical method is used. The result is, it is found that according to Riá¸Ä, isrÄiliyyÄt are just unfounded stories and not worth quoting. While the Bible in Riá¸Äâ€™s view is a holy book containing the New and Old Testament the truth of which is believed by the People of the Book themselves. In this case, Riá¸Ä believes that the source worth quoting is only one which is á¹£aá¸¥Ä«á¸¥ and marfÅ«â€™ from the Prophet. Whenever it has to be from the People of the Book, one should quote from the Bible even though Riá¸Ä himself realizes that there are many oddities in it.